DESIGN AND CONSTRUCTION OF NOISE DETECTION DEVICE WITH ARDUINO-BASED SOUND SENSOR MIC IN THE LIBRARY - Wahjudi, Dody; Darmawan, Isra' Nuur; Kholistianingsih; Rifadila Fahmi, Ananda (Journal of Electronic and Electrical Power Applications, 2024)
The library holds the meaning as a place where various information is disseminated, whether printed or recorded in various media such as books, magazines, computers, and others. The library is a public place that provides information that can be visited by anyone, both children and adults are allowed to visit the library. Not apart from library visitors consisting of children to adults, it is not uncommon for disorder to occur inside the library, one of which is noise that can disturb the tranquility inside the library. Unexpected or unwanted noise because it does not match the library context can cause discomfort and disturbance to library visitors. Therefore, based on the considerations above, researchers try to propose research entitled "Design of Noise Detection Device with Sound Sensor Mic in the Library Based on Arduino". The system used utilizes the Arduino UNO microcontroller equipped with DF Player and other supporting devices so that in practice this tool can provide warnings when noise reaches a certain level in order to maintain noise below the predetermined threshold. The result of this research is that this system can operate by detecting the noise level with the KY307 mic sensor then using the Arduino microcontroller to analyze and process sound data to produce information about the noise level. This data is then displayed on the LCD screen and connected to an audio tweeter to provide a warning if the noise level exceeds the threshold.